Cryopreservation of buffy coat derived platelets: Paired in vitro characterization using uncontrolled versus controlled freezing rate protocols. Issue 2 (21st December 2020) - Tynngård, Nahreen; Bell, Alice; Gryfelt, Gunilla; Cvetkovic, Stefan; Wikman, Agneta; Uhlin, Michael; Sandgren, Per
Abstract: Background: Cryopreserved platelets show a reduced recovery and viability after freezing and thawing including several ultrastructural and phenotypic deteriorations compared with liquid‐stored platelets. It is suggested that using Controlled‐Rate Freezing (CRF) can reduce variability and optimize the functionality profile for cells. The objective of the study is to compare cellular, metabolic, phenotypic and functional effects on platelets after cryopreservation using different freezing rate protocols. Study Design and Methods: To evaluate the possible effects of different freezing rate protocols a two‐experimental study comparing diverse combinations was tested with a pool and split design. Uncontrolled freezing of platelets in materials with different thermal conductivity (metal vs cardboard) was evaluated in experiment 1. Experiment 2 evaluated uncontrolled vs a controlled‐rate freezing protocol in metal boxes. All variables were assessed pre and post cryopreservation. Results: Directly after thawing, no major differences in platelet recovery, LDH, ATP, Δψ, CD62P, CD42b, platelet endothelial cell adhesion molecule and sCD40L were seen between units frozen with different thermal conductivity for temperature. In contrast, we observed signs of increased activation after freezing using the CRF protocol, reflected by increased cell surface expression of CD62P, PAC‐1 binding and increased concentration of LDH. Agonist induced expression of a conformational epitope on the GPIIb/IIIa complex and contribution to blood coagulation in an experimental rotational thromboelastometry setup were not statistically different between the groups. Conclusion: The use of a uncontrolled freezing rate protocol is feasible, creating a platelet product comparable to using a controlled rate freezing equipment during cryopreservation of platelets.